Evaluasi Fitur Tracking pada Pengalaman Pelanggan di Bisnis Reparasi Smartphone - Adittia Fathah (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
The aim of this research is to evaluate the tracking feature on customer experience using cell phone repair services. This research uses explanatory research method. The research sample taking method is the quota sampling method, namely 196 students at Sekolah Tinggi Teknologi Cipasung. Data collection was carried out by distributing questionnaires through the Google Form. The rating scale used is Likert. The data that has been collected is tested for its validity and reliability. The application used for data testing and visualization is Microsoft Excel. The results of data processing show that the resulting percentage value is between 80-100%. These results show consumers "Strongly Agree" that tracking services in the smartphone repair business are needed. The tracking feature can provide benefits and added value to the smartphone repair business so that it can provide a positive experience for consumers. With this research, it is hoped that every cellphone repair business will provide a tracking feature, so consumers can get information about their smartphone when it is repaired.